Functional infrared thermography imaging can be used to assess the effectiveness of Maxicam Gel® in pre-emptively treating transient synovitis and lameness in horses - Carvalho, Júlia Ribeiro Garcia de; Del Puppo, Debora; Littiere, Thayssa de Oliveira; Sales, Nathali Adrielli Agassi de; Silva, Ana Carolina Yamamoto; Ribeiro, Gesiane; Almeida, Ferdinando Nielsen de; Alves, Bruna Gomes; Gatto, Igor Renan Honorato; Ramos, Gabriel Vieira; Ferraz, Guilherme de Camargo (Frontiers in Veterinary Science, 2024)
Introduction Diagnosing and treating lameness in horses is essential to improving their welfare. In equine orthopedic practice, infrared thermography (IRT) can indirectly detect soreness. Non-steroidal anti-inflammatory drugs can treat painful and inflammatory processes in horses. Using IRT, the efficacy of meloxicam (Maxicam Gel®) was evaluated in pre-treating transient synovitis in horses induced by a middle carpal joint injection of lipopolysaccharides (LPS) from E. coli 055:B5 at a dose of 10 endotoxin units. Methods In a cross-over design, six healthy horses were randomly assigned to receive either 0.6 mg/kg of oral Maxicam Gel® (MAXVO) or a mock administration (control group, C) following a two-week washout period. IRT of the middle carpal joint, visual lameness assessment and joint circumference were recorded over time. Clinical and hematological evaluations were performed. Synovial fluid aspirates were analyzed for total nucleated cell count, total protein, and prostaglandin E2. A mixed effects analysis of variance was performed for repeated measures over time, followed by Tukey’s test. A multinomial logistic regression was conducted to determine whether there is a relationship between a thermography temperature change and the lameness score. Results There were no changes in joint circumference. The MAXVO group showed a lower rectal temperature 4 h after synovitis induction. The C group presented an increase in neutrophils and a decrease in total hemoglobin and hematocrit 8 h after induction. No changes were observed in the synovial fluid between groups. The horses that received meloxicam did not show clinically significant lameness at any time, while the C group showed an increase in lameness 2, 4, and 8 h after synovitis induction. Discussion IRT indicated that the skin surface temperature of the middle carpal joint was lower in horses who received meloxicam, suggesting a reduction in the inflammatory process induced by LPS. It was observed that the maximum temperature peaks in the dorsopalmar and lateropalmar positions can be utilized to predict the severity of lameness, particularly when the temperature rises above 34°C. Horses pre-treated with meloxicam showed either reduced or no indication of mild to moderate pain and presented a lowehr thermographic temperature, which indicates the effectiveness of Maxicam Gel® as an anti-inflammatory.